Solar-Powered Drip Irrigation Impacts on Crops Production Diversity and Dietary Diversity in Northern Benin. (June 2016) - Alaofè, Halimatou; Burney, Jennifer; Naylor, Rosamond; Taren, Douglas
Background: Meeting the food needs of Africa's growing population will require innovative and appropriate technologies whose effectiveness needs to be assessed. Objective: To evaluate the impact of Solar Market Gardens (SMGs) on crops production diversity and dietary diversity in the Kalalé district of Northern Benin. Methods: In 2007, SMGs were installed in 2 villages for women's agricultural groups as a strategy for enhancing food and nutrition security. Data were collected through interviews at installation and 1 year later from all women's group households (30–35 women/group) and from a random representative sample of 30 households in each village, for both treatment and matched-pair comparison villages. Results: Comparison of baseline and endline data indicated increases in the variety of fruits and vegetables produced and consumed by SMG women's groups compared to other groups. The proportion of SMG women's group households engaged in vegetable and fruit production significantly increased by 26% and 55%, respectively ( P < .05). After controlling for baseline values, SMG women's groups were 3 times more likely to increase their fruit and vegetable consumption compared with comparison non-women's groups ( P < .05). In addition, the percentage change in corn, sorghum, beans, oil, rice and fish purchased was significantly greater in the SMG women's groups compared to other groups. At endline, 57% of the women used their additional income on food, 54% on health care, and 25% on education. Conclusions: Solar Market Gardens have the potential to improve household nutritional status through direct consumption and increased income to make economic decisions.